Menggali Berpikir Kritis Siswa Kelas V Pada Pembelajaran Matematika Melalui Media Papan Ular Tangga Berbasis Budaya - Zakki Susanto, Moh.; Rita Fiantika, Feny (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Policies carried out by the education government over time have changed, especially the current curriculum which has changed to an independent curriculum. Teachers have an important role in the success of the applicable curriculum, especially teachers in implementing math learning. The independent curriculum for grade V mathematics has angle material which students believe is still difficult to learn because of the lack of using critical thinking skills, angle material is also related to mathematical problems in learning. Culture is often forgotten by students today, researchers have a solution, namely using learning media in the form of snakes and ladders boards containing cultures in Indonesia. This research uses descriptive qualitative research to explain in detail what happened during the research, the researcher chose one of the students, namely subject NP as a high ability representative. Subject NP fits the criteria for critical thinking skills in solving problems, starting from how to answer and provide reasons for his answers. The researcher believes that the use of learning media is very effective in improving student understanding when students do not understand what is being learned.